Research on the Path of Improving the Digital Teaching Ability of College Teachers under the Background of Education Digitalization - Hou, Qiuping (Education Insights, 2026)
With the advancement of technologies such as artificial intelligence and big data, the digitalization of education has become a key direction in higher education reform, imposing new requirements on teachers' professional development. Teachers' digital teaching competence refers to the comprehensive ability to integrate technology and teaching in a digital environment, encompassing five dimensions: technology application, instructional design, resource integration, data analysis, and ethical security, characterized by comprehensiveness and dynamism. Current challenges include outdated concepts, uneven technology application, weak teaching integration, insufficient data literacy, and an incomplete training system. This study proposes a multidimensional collaborative approach: updating concepts, tiered training, enhancing instructional design, strengthening data literacy, improving incentive mechanisms, and building professional communities, to provide references for the development of teachers' digital teaching competence.